NORMA PERKEMBANGAN MOTOR MILESTONE ANAK SEHAT DAN BERGIZI BAIK DALAM RANGKA PENGEMBANGAN SUATU RUJUKAN - Abas B. Jahari; Heryudarini Harahap; Yekti Widodo; Yayah K. Husaini; Soesmalijah Soewondo (Persagi, 2006)
Norm of Motor Milestone Achievements In Healthy and Well Nourished Children Leading To The Development A Reference.Background: The prevalence of malnutrition is still high in Indonesia, and one of its functional consequences is level of the intelectual capacity of children. Motor development is an essential of cognitive performance, and it is generally believed related with nutritional status of children, however very few studies had been carried out in the field condition.Objectlves: To describe the ceiling of motor milestone achievements of healthy and well nourished children aged 3-18 months in the development of norms for Indonesian children.Methods: The study was conducted in 4 big cities: Surabaya, Malang, Bandung and Bogor in 2100 healthy and well nourished children aged 3-18 months came from high SES (socio-economic status) families who had no constraints on achieving normal growth and development. There were 17 milestones observed by well trainned enumerators following standard procedure. Analysis of percentiles 5, 10, 50, 90, and 95 for age against motor achievement were carried out for all children.Results: The difference in the attainment of the ceiling of motor milestones between males and females were not significant at any points of observation, therefore sex combined norm curve of motor development for children aged 3-18 months was ilustrated.Conclusions: The norm of motor milestone development for Indonesian children aged 3-18 months has been developed. Before being used as a reference, it needs to be evaluated or it is reliability and feasibility.Keywords: motor milestone, motor development, reference of motor development.